Mirtazapine is a functional antagonist at cardiac human H1-histamine receptors - Thanh Hoai Pham; Jonas M. A. Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Mirtazapine is an atypical tetracyclic antidepressant drug that binds to several monoamine neurotransmitter receptors. For instance, mirtazapine binds to H 1 -histamine receptors in vitro and in the brain of patients in vivo. Here, we hypothesize that mirtazapine is an antagonist at human cardiac H 1 -histamine receptors. To test this hypothesis, we measured force of contraction in isolated electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult transgenic mice with cardiomyocyte-specific overexpression of the human H 1 -histamine receptor (H 1 -TG). These findings were compared with those in wild-type littermate mice (WT). Finally, we measured the force of contraction in isolated electrically stimulated right atrial muscle strips (HAP) gotten from adult patients who were undergoing bypass surgery. Mirtazapine concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in LA and RA from H 1 -TG. Importantly, mirtazapine (starting at 100 nM) concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in HAP. We thus conclude that mirtazapine can antagonize human cardiac H 1 -histamine receptors at therapeutic drug concentrations, and thus, mirtazapine may have cardiac untoward effects in psychiatric patients.